Modern Theoretical Approaches to Teaching Foreign Language - Turaeva Guzal (Zien Journals, 2022)
The article discusses the main stages of the formation of a communicative approach in Uzbek linguistic education. The authors also describe the current state of communicative training and the prospects for its further development.
Keywords: communicative approach; communicative education; teaching foreign languages; communication theory